The development of the concept of time in Slavic languages - Rytter, Grażyna (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The history of determining time in Slavic languages is the result of abstract and simultaneously classifying activities of human consciousness. The methods of marking time reflect the recognition of the surrounding world based on a specific experience of tribal and family life, on observation of cyclical changes of seasons in nature, phases of the moon, sunrise after sunset, day and night. Christianity spread among Slavs the ways of determining time, that were typical of ancient culture.